2011
DOI: 10.3109/08958378.2011.643417
|View full text |Cite
|
Sign up to set email alerts
|

Government and Navy knowledge regarding health hazards of asbestos: A state of the science evaluation (1900 to 1970)

Abstract: We evaluated dozens of published and unpublished documents describing the knowledge and awareness of both the scientific community and governmental entities, particularly the US Navy, regarding the health hazards associated with asbestos over time. We divided our analysis into specific blocks of time: 1900-1929, 1930-1959, and 1960-1970. By 1930, it was clear that high occupational exposure to asbestos caused a unique disease (asbestosis). Between about 1938 and 1965, a considerable amount of exposure and epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Malignant mesothelioma has long been known as cancer closely linked to occupational exposure to asbestos fibers. A significantly higher incidence of mesothelioma compared with the general population was found among workers handling asbestos, like miners (1), workers in shipyards (2), and even workers' relatives or residents in areas near the asbestos factories (3). Asbestos is a general term used in the mineral commodity field to identify 5 amphibole and 1 serpentine silicate fibers that were extensively used until the end of the last century when asbestos was banned or strictly regulated in the Western world and Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant mesothelioma has long been known as cancer closely linked to occupational exposure to asbestos fibers. A significantly higher incidence of mesothelioma compared with the general population was found among workers handling asbestos, like miners (1), workers in shipyards (2), and even workers' relatives or residents in areas near the asbestos factories (3). Asbestos is a general term used in the mineral commodity field to identify 5 amphibole and 1 serpentine silicate fibers that were extensively used until the end of the last century when asbestos was banned or strictly regulated in the Western world and Japan.…”
Section: Introductionmentioning
confidence: 99%
“…According to Roggli et al (2002) Table 1 of this paper, railroad workers ranked seventh in the top 12 industry types based on their large (1445 cases) sample of mesothelioma deaths. Asbestos exposure and US Navy: Until efforts to use substitute materials for asbestos on US Navy ships (and ships from other nations) and enhanced asbestos control measures accelerated in the 1970s (Anonymous, 1979;Franke & Paustenbach, 2011;Harries, 1968;Mangold et al, 1970;Rushworth, 2005;Strand et al, 2010;Twight 1991;Winer & Holtgren, 1976), both amosite and chrysotile asbestos was used extensively on US Navy ships. Nearly all Navy personnel aboard ships had some asbestos exposure, even in berthing quarters and mess halls, particularly prior to 1980.…”
Section: Mesotheliomamentioning
confidence: 99%
“…19 With mounting evidence of the risks of lung disease associated with asbestos, the Navy adopted stricter measures such as respirators to counter these risks. During the 1930s, studies demonstrated an association between occupational exposure to asbestos fibers and a fibrosing lung disease known as asbestosis.…”
Section: What Occupational Lung Disease and Malignancy Has Been Assocmentioning
confidence: 99%